Looking the other way: Some old and new data on amphorae and trade from Lusitania in the territory of Onuba Estuaria (western Baetica) - de Almeida, Rui Roberto (Rei Cretariae Romanae Fautorum Acta, 2022)
The western part of Baetica is nowadays very well known, particularly its salt-fish industries. Naturally, investigation has focused on the local production, thereby relegating the matter of consumption into second place. A programme of regional research begun recently is studying some ancient collections (of unknown provenience) in the Museum at Huelva, some private collections from well-known sites (mainly El Eucaliptal) and several other individual finds collected by fisherman, the majority from the area between the mouths of the rivers Odiel and Guadiana (broadly from the coastal area of Punta Umbria). This work permits us to recognize a significant consumption of products from other areas, especially from the ‘neighbouring’ province of Lusitania. The main goal of this paper is to set out the evidence of this trade, review some of the amphorae in the collections and present new finds, particularly from a petrographical angle. In this way one may secure a first impression on the evolution of the trade with Lusitania.